CD4 cell activation with the CD8 marker and metallothionein expression in the gills of cadmium-exposed mosquito fish (Gambusia affinis Baird and Girard 1853) juveniles - Moh Awaludin Adam; Agoes Soegianto; Carolyn Melissa Payus; Ach Khumaidi; Ramli Ramli; Ernawati Ernawati; Irawati Mei Widiastuti; Era Insivitawati; Yenny Risjani (Elsevier B.V., 2022)
This experiment aimed to determine how Cd exposure impacts CD4 cell activation, macrophage cells, pinocytosis activity, metallothionine expression, and Cd levels in juvenile Gambusia affinis gills. Four treatment groups were used, with one control and treatments A, B, C, and D at dosages of 0.03 mg/L, 0.023 mg/L, 0.015 mg/L, and 0.008 mg/L, respectively. The results showed that the number of CD4 with CD8 cell markers differed significantly from each treatment compared to the control (0.33%). The value in A, namely 0.54%, was the highest, followed by B, C, and D of 0.46%, 0.44%, and 0.42%, respectively. The number of macrophages increased as the Cd level of the medium increased, as did the activity of pinocytosis. Furthermore, the immunofluorescence test on the gills with the Anti-MT Mouse and goat IgG fluoresce in Rhodamine on the gills showed that luminescence increased with increasing Cd levels in the gills. Similarly, the MT intensity increased at Cd-exposed gills as compared to the control. As the Cd level in the gills increased, the MT levels ascended significantly.